Evaluasi Perencanaan Pembangunan Perpustakaan Daerah dalam Meningkatkan Literasi Masyarakat: (Studi Kasus Kabupaten Serang) - Dita Amalia; Laeli Nur Khanifah; Angeli Ramadhani; Siti Alya Aryanti; Azalia Salsabila (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Regional library development is an important part of local government efforts to improve public access to information and literacy services. This study aims to evaluate the planning of the Regional Library development in Serang Regency in supporting community literacy improvement. The research employed a qualitative method with a case study approach. Data were collected through in depth interviews with the Regional Development Planning, Research, and Innovation Agency (BAPPERIDA) of Serang Regency and supported by literature studies from relevant documents and publications. The analysis was conducted using William N. Dunn’s policy evaluation framework, which consists of effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that the library development planning has been integrated into regional development planning documents and supported by funding from the central government through the Special Allocation Fund. The selection of the library location considered land availability, accessibility, and proximity to educational institutions. The study also found challenges related to supporting facilities and the limited number of librarians. Although the physical construction has been completed, the library had not yet been fully operational at the time of the research, making its impact on community literacy impossible to assess directly. The study implies that operational readiness, human resources, and sustainable literacy programs are essential to maximize the benefits of the regional library for the community.